Investigation of different degradation methods to prepare liquid epoxidized natural rubber for coating applications / Pejvak Rooshenass - Pejvak , Rooshenass (2017)
Epoxidized natural rubber (ENR) is a very significant polymer due to its outstanding mechanical performance besides low cost and great mechanical properties. However, ENR has high molecular weight which limits its solubility and its processability. This study concerns the degradation of ENR to shorter chain lengths to form liquid epoxidized natural rubber (LENR) employing 5 different methods, i.e. (i) mechanical milling, (ii) chemical degradation initiated by potassium peroxodisulfate, (iii) photo-oxidation initiated by ultra violet (UV), (iv) oxidative degradation by periodic acid (H5IO6) and (v) oxidative degradation by potassium permanganate (KMnO4). The first three methods [(i), (ii) and (iii)] break-down of ENR is via free radicals, but at different rates and mechanisms. FTIR and NMR results showed that in these three methods ketone, aldehyde, carboxylic acid, ester and lactone groups were observed; however only during the UV degradation a hydrofuranic structure was formed. The oxirane group was not affected significantly during the degradation, indicating that the chain scissions had occurred predominantly via the double bonds. Comparison of the NMR and FTIR spectra of degradation products showed that UV degradation induced more carbonyl and hydroxyl groups to the backbone of the ENR. Increasing of oxygen concentration did not enhance the efficiency in UV degradation method. Mastication with two roll mill produced LENR with greatest degree of unsaturation and less amounts of polar groups. The last two methods [(iv) and (v)] degraded ENR through chemical oxidative degradation. The products of these two methods were compared with LENR obtained from degradation initiated by UV irradiation. Degradation of ENR by KMnO4 and UV irradiation proceeded mostly by attack via double bond, as confirmed by NMR spectroscopy irradiation proceeded mostly by attack via double bond, as confirmed by NMR spectroscopy whereby a decrease in the ratio peak areas of epoxy methine proton to olefinic methine proton was observed. At concentration of above 0.044 mol H5IO6 per hundred grams of rubber (mphr), degradation occurred by ring opening of the oxirane group as confirmed by the NMR of the LENR which showed an increase in the ratio peak areas of olefinic methine proton to epoxy methine proton. The LENR obtained by H5IO6 has more ketone groups while the LENR from degradation by KMnO4 has more ester groups. Cyclization of isoprene unit was only observed during the degradation by H5IO6. Among these methods, H5IO6 has achieved the fastest rate of degradation and lowest Mn under comparable conditions. For coating application, methyl methacrylate (MMA) was graft copolymerized onto LENR using UV radiation and benzophenone as photo initiator. The best grafting efficiency was observed by 0.84 parts per hundred resin (phr) of benzophenone. DSC thermograms showed a small positive shift in Tg of LENR compared to ENR 25. LENR-graft-PMMA showed a great increase in Tg (42ºC), because incorporation of hard segments of PMMA onto LENR. The obtained PMMA-graft-LENR was cured with three different amines and evaluated as coatings materials. Overall, the best results for coating performances were observed by curing of PMMA-graft-LENR with a cycloaliphatic amine. This type of coating demonstrated the best hardness, adhesion, water and salt resistances.